2015
DOI: 10.1097/md.0000000000001251
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Cardiovascular Polypharmacy Is Associated With the Risk of Acute Kidney Injury in Elderly Patients

Abstract: Polypharmacy is common in the elderly due to multimorbidity and interventions. However, the temporal association between polypharmacy and renal outcomes is rarely addressed and recognized. We investigated the association between cardiovascular (CV) polypharmacy and the risk of acute kidney injury (AKI) in elderly patients.We used the Taiwan National Health Insurance PharmaCloud system to investigate the relationship between cumulative CV medications in the 3 months before admission and risk of AKI in the elder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 40 publications
(43 reference statements)
2
41
1
1
Order By: Relevance
“…However, in addition to those factors, we demonstrated that polypharmacy significantly raised the odds of having CKD. Polypharmacy has been shown to be associated with an increased risk for acute kidney injury [18] , but only few, small studies have addressed the role of polypharmacy in CKD [19] . Polypharmacy, defined as the use of ≥ 5 drugs, is particularly common in the elderly [22,38] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in addition to those factors, we demonstrated that polypharmacy significantly raised the odds of having CKD. Polypharmacy has been shown to be associated with an increased risk for acute kidney injury [18] , but only few, small studies have addressed the role of polypharmacy in CKD [19] . Polypharmacy, defined as the use of ≥ 5 drugs, is particularly common in the elderly [22,38] .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we aimed to assess the awareness of CKD in our cohort and to identify possible risk factors, with particular interest in polypharmacy. While polypharmacy is an established risk factor for acute kidney injury in elderly patients [18] , only few studies have studied the relationship between polypharmacy and the incidence and prevalence of CKD [19] .…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps the most relevant examples are ACE inhibitors and ARBs, which are associated with functional AKI, particularly in the setting of acute hypovolaemia 5,[125][126][127] . These agents are frequently prescribed, particularly in the elderly 128 .…”
Section: Ace Inhibitors and Arbsmentioning
confidence: 99%
“…They included medical history, medication history, 26 preoperative cardiovascular status, anesthesia and surgery-related factors, intraoperative hemodynamic variables and laboratory findings, including postoperative nadir platelet count.…”
Section: Perioperative Clinical Variables and Echocardiographic Datamentioning
confidence: 99%